2016
DOI: 10.2983/035.035.0410
|View full text |Cite
|
Sign up to set email alerts
|

Quality Trait Signature at Archipelago Scale of the Cultured Pearls Produced by the Black-Lipped Pearl Oyster (Pinctada margaritiferaVar.cumingi) in French Polynesia

Abstract: In French Polynesia, the aquaculture of Pinctada margaritifera (Linnaeus, 1758) covers a large maritime exploitation area, spread over nearly 20 degrees latitude and longitude, with numerous pearl farms located in three archipelagos (Gambier, Society, and Tuamotu). As these archipelagos have specific seasonal temperature patterns each year, pearl oysters are subject to disparate and contrasting environmental regimes. This study aimed to examine the specificity of commercial pearl quality traits (n ¼ 2,236 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
4
10
1
Order By: Relevance
“…Inversely, it was in the GMR site, that the lowest amount of pearls with up to 10 surface defects was observed in comparison to RRR. This result was consistent with results found by Ky et al (2016b), and…”
Section: Accepted Manuscriptsupporting
confidence: 94%
See 4 more Smart Citations
“…Inversely, it was in the GMR site, that the lowest amount of pearls with up to 10 surface defects was observed in comparison to RRR. This result was consistent with results found by Ky et al (2016b), and…”
Section: Accepted Manuscriptsupporting
confidence: 94%
“…This inter-mantle section amplitude of variation was less than the inter-site variation, which suggests that the RRR location is the most appropriate for pearl size improvement. This was consistent with another recent study (Ky et al, 2016b), which confirmed the growth potential in favour of Tuamotu archipelago (where RRR atoll was located) compared with Gambier archipelago (where the GMR island is located). Indeed, the nacre deposition rate was faster in RRR than in GMR, because the average temperature in lagoons of Tuamotu is warmer than in the lagoon of Gambier (Ky et al, 2016b).…”
Section: Nacre Deposition Ratesupporting
confidence: 93%
See 3 more Smart Citations